Green Marketing Communication Strategy on Le Minerale Product Purchasing Decision - Aprilianty, I Dewa Ayu Paramitha; Manggala RS, Aditya; Erma Mertaningrum, Ni Luh Putu; I Wayan Sugiartana (SEAN Institute, 2025)
This research examines the influence of sustainable marketing communications or green marketing communications on Generation Z's purchasing decisions for Le Minerale bottled drinking water products in Denpasar City. This research employed a quantitative methodology, gathering data through questionnaires distributed to 60 Generation Z individuals who consume Le Minerale. The study utilized a purposive sampling method, categorized under non-probability sampling methods. With the aid of SmartPLS software, the data was examined using the Partial Least Square (PLS) method. The data analysis results indicate that the p-value for hypothesis testing with path coefficients is 0.000, or less than 0.05. Therefore, if the p-value is less than 0.05, it suggests a direct relationship between the variables under analysis, in accordance with the guidelines for hypothesis testing using path coefficients. With a p-value of 0.000 and an effect size of 0.780, the t statistic in this investigation was reported at 22,000. Since the p-value is less than 0.05 and the t statistic is much higher than the 2.00 cutoff, it is possible to accept H1 and reject H0. The findings reveal that eco-friendly marketing communication significantly and positively influences purchasing decisions. Generation Z, who have high environmental awareness, tend to be more supportive of brands that actively communicate sustainable practices and transparency in their products.